STRATEGI KOMISI PEMILIHAN UMUM KALIMANTAN TIMUR DALAM MENINGKATKAN ANGKA PARTISIPASI PEMILIH PADA PEMILU SERENTAK TAHUN 2024 - Rohaimi, Emi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2022)
Strategy of the General Election Commission (KPU) of East Kalimantan in Increasing Voter Participation Rates in the 2024 Simultaneous Elections, Emi Rohaimi, Postgraduate Masters Program in Public Administration at Mulawarman University, February 2022, Prof. Dr. Hj. Aji Ratna Kusuma, M.Si and Prof. Dr. Hj. Hartutiningsih, M.Si.This study aims to produce a choice of strategies and efforts that can be considered by the East Kalimantan KPU in increasing voter turnout in the 2024 election. The study uses a SWOT analysis model in a qualitative approach.The results of the study show: 1. That there are a number of strategic options for the East Kalimantan KPU, namely (1) SO: regulation, internal-external cooperation, completing infrastructure, optimizing funding sources. (2) WO: optimizing human resources with stakeholders and new partners, strengthening communication and coordination partnerships, controlling critical thinking, and developing creativity. (3) ST: regulation suppresses negative competition, HR suppresses hardline and transactional group thinking; National government and local government funding; complete the facilities and infrastructure; strategies and methods of controlling critical thinking in urban communities. (4) WT: preventing negative competition for election participants, optimizing ethok officers or volunteers as well as driving cadres, developing Regency/City KPU creativity; communication and coordination prevent misunderstandings; critical and intelligent thinking control partnership; 2. Efforts that can be made by the East Kalimantan KPU to increase voter participation rates. (1) Internal strengthening, utilizing and empowering strengths and minimizing weaknesses. Improving the quality of human resources, partnerships with educational and political institutions, as well as suffrage education. (2) Paying attention to national and regional dynamics to deal with external conditions with the assistance of Regency/Municipal KPU for well-targeted socialization. Keywords: Strategy to increase voter participation, General Election.